Effect of hydrated sodium calcium aluminosilicate on the prevention of the toxic effects of ochratoxin - Santin, E. [UNESP]; Maiorka, A. [UNESP]; Krabbe, E. L. [UNESP]; Paulillo, A. C. [UNESP]; Alessi, A. C. [UNESP] (Elsevier, 2002)
We studied the efficacy of hydrated sodium calcium aluminosilicate (HSCAS) as an inhibitor of the toxic effects of ochratoxin in broilers from 1 to 42 d of age. A total of 288 broilers was distributed into four treatments with four replicates of 18 birds each: T1, control; T2, 0.25% HSCAS; T3, 2 ppm of ochratoxin; T4, 0.25% HSCAS + 2 ppm ochratoxin. The parameters evaluated were feed intake; weight gain; feed conversion; relative weights of the liver, kidneys, and bursa; and serum levels of Ca, P, total protein (TP), aspartate aminotransferase (AST) and γ-glutamiltransferase (GGT). Ochratoxin in the diet negatively affected (P < 0.05) all performance parameters evaluated when the birds were 21 and 42 d of age. However, HSCAS did not affect performance, and there was no interaction between HSCAS and dietary ochratoxin. The liver and the kidneys of birds fed ochratoxin with or without HSCAS were relatively heavier (P < 0.05) than those of the control birds, demonstrating the influence of ochratoxin, but not of HSCAS, on the relative weight of these organs. Although the bursa of birds exposed to ochratoxin with or without HSCAS had a lower relative weight as compared to control birds, the difference was not significant. Ca, P, and TP serum levels were lower (P < 0.05) in birds exposed to ochratoxin, whereas AST and GGT levels were higher (P < 0.05) in these birds. These results reflect that ochratoxin in the diet impaired the productivity indexes and that HSCAS did not improve these parameters.
Keywords: Broiler; Hydrated sodium calcium aluminosilicate; Ochratoxin; Performance